Hirschsprung-Associated Enterocolitis: Transformative Research from Bench to Bedside - Zhang, Zhen; Li, Bo; Jiang, Qian; Li, Qi; Pierro, Agostino; Li, Long (European Journal of Pediatric Surgery, 2022)
Hirschsprung disease (HSCR) is a congenital disease that is characterized by the absence of intrinsic ganglion cells in the submucosal and myenteric plexuses of the distal colon and is the most common cause of congenital intestinal obstruction. Hirschsprung-associated enterocolitis (HAEC) is a life-threatening complication of HSCR, which can occur either before or after surgical resection of the aganglionic bowel. Even though HAEC is a leading cause of death in HSCR patients, its etiology and pathophysiology remain poorly understood. Various factors have been associated with HAEC, including the mucus barrier, microbiota, immune function, obstruction of the colon, and genetic variations. In this review, we examine our current mouse model of HAEC and how it informs our understanding of the disease. We also describe current emerging research that highlights the potential future of HAEC treatment.
Keywords: Hirschsprung's disease; Hirschsprung-associated enterocolitis; Pathophysiology; translational research